Healthcare Personnel Readiness for Telemedicine Adoption:Advancing Service Quality at XSemarang Hospital: Technology Readiness Index - Rafli Hz, Muhammad; Wulan, Widya Ratna; Kurniadi, Arif; Setiono, Oki (International Journal of Health Literacy and Science, 2025)
The use of telemedicine in Indonesia has increased rapidly with the COVID-19 pandemic. To date, there are 300,000 users. The obstacle to implementing telemedicine for small medical facilities is that telemedicine is too expensive because it requires a lot of money to build and maintain it. The purpose of this study is to describe the readiness of health workers related to the use of telemedicine as a medium to support the quality of health services at Bhakti Wira Tamtama Hospital. This study was conducted from May to June 2024. The research method used was descriptive quantitative. This study measures the readiness of health workers according to the TRI (Technology Readiness Index) method. The subjects of this study were 23 respondents selected by accidental sampling. The results showed that most respondents' optimism towards telemedicine was good (87%). However, most respondents also felt uncomfortable with the use of telemedicine (73.9%) and felt unsafe using telemedicine (87%). Hospitals should provide more in-depth training on telemedicine technology and platforms for healthcare workers.